2000
DOI: 10.1136/jech.54.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation and childhood obesity: a cross sectional study of 20 973 children in Plymouth, United Kingdom

Abstract: Objective-To study the association between socioeconomic deprivation and childhood obesity. Design-Cross sectional study. Results-Plymouth had a rate of childhood obesity two and half times that expected nationally (5% v 2%). The obesity prevalence increased with age, being almost double in the oldest age quarter (boys 6.2%; girls 7.0%), compared with the youngest age quarter. Within Plymouth, there was a significant trend for higher rates of obesity related to increasing deprivation in both boys (p=0.017) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
104
4
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 29 publications
13
104
4
4
Order By: Relevance
“…A summary of the 45 studies satisfying the criteria for this review is presented in the appendices (Supplementary Tables online) according to the format of adiposity variable (Appendix 1 (Studies 1-35): categorical; Appendix 2 (36-45): continuous) and treatment of gender (Appendix 1a (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and 2a (36)(37)(38)(39)(40): combined; Appendix 1b (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 2b (41)(42)(43)(44)(45): stratified) in the data analysis. At least one of the criteria for this review was not satisfied by 2,348 studies that were eliminated in the twostep procedure described in the Methods and Procedures section.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…A summary of the 45 studies satisfying the criteria for this review is presented in the appendices (Supplementary Tables online) according to the format of adiposity variable (Appendix 1 (Studies 1-35): categorical; Appendix 2 (36-45): continuous) and treatment of gender (Appendix 1a (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and 2a (36)(37)(38)(39)(40): combined; Appendix 1b (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and 2b (41)(42)(43)(44)(45): stratified) in the data analysis. At least one of the criteria for this review was not satisfied by 2,348 studies that were eliminated in the twostep procedure described in the Methods and Procedures section.…”
Section: Identification Of Studiesmentioning
confidence: 99%
“…Other studies have considered multiple SES factors as an index of deprivation. For example, studies using the Townsend deprivation score (an index score based on a combination of adult unemployment, household size, and car and home ownership) have shown that children from more deprived areas have a higher risk of obesity (despite lower birth weights) 95,163 . However, if the deprivation index is based on the electoral ward of the school (rather than the home), no relationship with childhood obesity is present 164 .…”
Section: The Neighbourhood Environmentmentioning
confidence: 99%
“…1,2 In addition, low socioeconomic status (SES) is frequently associated with higher rates of overweight. [3][4][5][6] Thus, the search for causes and potential interventions to decrease these disparities and reduce the prevalence of overweight is crucial.Breastfeeding has been reported as being protective against obesity, but this association is somewhat controversial. Whereas several studies found significantly lower obesity rates among those who were breastfed as infants 7-11 and a dosage-related effect of breastfeeding, 12-17 not all studies supported these findings.…”
mentioning
confidence: 99%
“…1,2 In addition, low socioeconomic status (SES) is frequently associated with higher rates of overweight. [3][4][5][6] Thus, the search for causes and potential interventions to decrease these disparities and reduce the prevalence of overweight is crucial.…”
mentioning
confidence: 99%